EARNING QUALITY AND TAX PLANNING: EVIDENCE ON INDONESIA LISTED COMPANY - Theresia Trisanti (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2019)
This study aims at determining the effect of tax planning, profit growth and firm size on earnings quality and also to test the effect of tax planning as moderating variable to influence of profit growth, size and earnings quality. This research is different from previous research, the difference is that this research makes tax planning as a moderation so that it can see whether tax planning can strengthen or weaken the influence of profit growth and firm size on earnings quality.The data used is secondary data from Indonesian listed manufacturing companies, hypothesis testing using regression model with partial least square test. This study shows that profit growth directly affects earnings quality and firm size does not affect earnings quality, but after being moderated by tax planning the size of the company has a significant effect on earnings quality. This research finding add understanding in assessing earnings quality with the influence of tax planning so that it can be used as a decision-making consideration.